Voltage response characterization of grid-forming wind power systems - Li, Qun; Li, Qiang; Tang, Weijia; Wang, Chenggen (Frontiers in Energy Research, 2024)
The widespread integration of wind turbines poses voltage stability challenges to power systems.To enhance the ability of wind power systems to actively support grid voltage, grid-forming control techniques are increasingly employed. However, current research primarily focuses on voltage stability challenges at the point of common coupling in wind power systems, lacking thorough investigation into the system voltage response characterization. This paper establishes the voltage response model of a grid-forming wind power system. Based on this model, mathematical derivation and theoretical analysis are conducted, and the effect factors of the voltage at the point of common coupling are investigated. Further, a voltage stabilization method is explored by adjusting above effect factors. Finally, based on the MATLAB/SIMULINK platform, the simulation verification of each effect factor is carried out. The results indicate that voltage response characterization obtained by the theoretical analysis and simulation is similar and that the proposed method is valid.